PENGARUH PERCEIVED OF BENEFIT DAN E-TRUST TERHADAP MINAT MENGGUNAKAN QRIS - Sadana Devica; Mentari Septynaputri Widodo (Universitas Katolik Darma Cendika, 2023)
This study aims to examine whether there is an influence between perceived benefits and e-trust on the intention to use QRIS. The data collection technique in this study was by using non-probability sampling with the method of determining the sample, namely judgment sampling or purposive sampling techniques. The number of respondents in this research are 155 respondents. Furthermore, the collected data has been tested for construct validity and reliability and processed using SEM (Structural Equation Modeling) analysis. To test the construct validity of exogenous variables, researchers use the value of the loading factor. As for the reliability test, the researcher used the Cronbach Alpha value. Researchers have also conducted a model fit test to ensure that the research model used is included in the very good category (fit). The results of this study indicate that perceived benefit and e-trust have a positive and significant effect on interest in using QRIS. The results of this study also show that the millennial generation can accept new innovations created by digital payment applications.